2015
DOI: 10.4274/tjo.48379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Systemic Infliximab Therapy in Patients with Sjögren’s Syndrome

Abstract: Objectives:To investigate the effect of systemic infliximab therapy on tear function tests and the ocular surface in patients with Sjögren’s syndrome secondary to various autoimmune diseases.Ma­te­ri­als and Met­hods:This prospective study included 22 eyes of 22 patients with Sjögren’s syndrome who began treatment with systemic infliximab. Tear film break-up time (TBUT), anesthetized Schirmer’s 1 test, fluorescein staining test, and Ocular Surface Disease Index (OSDI) scores were recorded before treatment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…Infliximab and etanercept, which both target TNF-α, have been shown to improve ocular fatigue symptoms, but were ineffective in patients with dry eyes and dry mouth. Currently, a multicenter phase II clinical trial of infliximab is underway, but so far, xerosis symptoms and the degree of salivary gland infiltration were not improved and there were serious adverse reactions, such as transfusion reaction, autoimmune liver disease, and pneumococcal septicemia ( 127 ). In a clinical trial of subcutaneously applied etanercept in 15 SS patients, the salivary and lacrimal gland functions were not significantly improved, and some individuals had local side effects ( 128 ).…”
Section: Targeting Cytokines In Ssmentioning
confidence: 99%
“…Infliximab and etanercept, which both target TNF-α, have been shown to improve ocular fatigue symptoms, but were ineffective in patients with dry eyes and dry mouth. Currently, a multicenter phase II clinical trial of infliximab is underway, but so far, xerosis symptoms and the degree of salivary gland infiltration were not improved and there were serious adverse reactions, such as transfusion reaction, autoimmune liver disease, and pneumococcal septicemia ( 127 ). In a clinical trial of subcutaneously applied etanercept in 15 SS patients, the salivary and lacrimal gland functions were not significantly improved, and some individuals had local side effects ( 128 ).…”
Section: Targeting Cytokines In Ssmentioning
confidence: 99%
“…Several other agents have been studied in SS, but not necessarily in relation to dry eye. This includes anti-inflammatory agents infliximab and etanercept, which target TNF-a, and anakinra, an IL-1 antagonist [ 50 , 51 ]. Tocilizumab, an IL-6 receptor agonist, showed no impact on immunoglobulins, complement, or systemic disease activity, which suggested that IL-6 may not be a main contributor to peripheral B-cell activation in SS [ 52 ].…”
Section: Novel Treatment Modalities and Advances In Drug-delivery Sys...mentioning
confidence: 99%